Endoscopic transsphenoidal approach in the diagnosis and treatment of chiasmosellar germinomas - M. A. Kutin; D. V. Fomichev; A. N. Shkarubo; I. V. Chernov; O. I. Sharipov; D. N. Andreev; D. B. Ismailov; N. I. Mikhaylov; G. L. Kobyakov; Yu. Yu. Trunin; L. I. Astafieva; A. A. Poddubsky; et al. (Опухоли головы и шеи)
Introduction. According to the recommendations of Russian and international professional associations, treatment of germinomas can be initiated without histological verification of the diagnosis, since it can be based on biochemical tumor markers. However, patients with brain germinomas usually have normal levels of these markers; therefore, histological verification is required. Stereotactic biopsy and transcranial biopsy are sometimes associated with a risk of damage to crucial anatomical structures. Currently, both biopsy and total removal of sellar and parasellar tumors can be performed via endoscopic endonasal approach. The study objective is to demonstrate the possibility of using endoscopic transsphenoidal approach for biopsy and total removal of chiasmosellar germinomas. Materials and methods. Thirteen patients with primary chiasmosellar germinomas underwent endoscopic endonasal interventions in N. N. Burdenko National Medical Research Center for Neurosurgery between 2010 and 2017. The “Germinoma-2008” protocol was used in the subsequent treatment of these patients. The male to female ratio was 2.25 : 1; mean age was 21.1 years (6–38 years).Results. The surgery volume varied between biopsy (n = 4) and partial (n = 5) or complete (n = 4) tumor removal. The diagnosis was histologically verified in all patients. None of the patients developed liquorrhea and / or meningitis in the postoperative period, which suggests that the surgery was effective and safe. Conclusion. The endoscopic endonasal approach for histological verification of the diagnosis and removal of chiasmosellar germinomas is safe and effective.